DISSOLVED ORGANIC CARBON IN SEA ICE AND SEAWATER OF SAROMA KO LAGOON AND RESOLUTE PASSAGE (ABSTRACT) (16th Symposium on Polar Biology) - / クドウ, サカエ; /; タグチ, サトル; SMITH, Ralph E. H.; KUDOH, Sakae; GOSSEELIN, Michel; ROBINEAU, Brigitte; TAGUCHI, Satoru (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper